The Impact of Dr Green Foliar Fertilization on Plant Health During the Growing Period as well as on the Potato Yield and Quality (Jelly Variety) (Agricultural Engineering, 2016)
The potato (Solanum tuberosum L.) is one of the four major crops in Poland. In 2013 the area used for potato cultivation in Poland reached 270 thousand hectares. Among the important factors influencing the potato yield and quality are: soil cultivation and protection of plants. One of the most essential factors affecting the potato yield and quality is fertilization. The aim of the field trials carried out in 2014 on experimental potato plots was to determine the effect of Dr Green foliar feed nutrients on plant health and on potato quality and yield (Jelly variety). The results of the studies and observations revealed that the application of Dr Green Ziemniak, Dr Green Start and Dr Green Energy foliar feeds favourably affected the quality, yield and structure of Jelly potato tuber crop.